2016
DOI: 10.4240/wjgs.v8.i11.761
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for spontaneous and postoperative sclerosing mesenteritis

Abstract: Sclerosing mesenteritis is a rare pathology with only a few described cases in the literature. The etiology is unclear; however, several potential triggers, including abdominal surgery and abdominal trauma, have been discussed. The pathology includes a benign acute or chronic inflammatory process affecting the adipose tissue of the mesenterium. Despite it being a rare disease, sclerosing mesenteritis is an important differential diagnosis in patients after abdominal surgery or patients presenting spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Because sclerosing mesenteritis is an inflammatory disease of unknown origin, treatment is based on immunosuppressive agents, including glucocorticoids [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because sclerosing mesenteritis is an inflammatory disease of unknown origin, treatment is based on immunosuppressive agents, including glucocorticoids [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, sclerosing mesenteritis is a self-limited disease, which is why asymptomatic cases are left untreated. In patients that present symptoms, therapeutic options include immunosuppressive agents and surgery [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 92 patients at Mayo Clinic with SM, approximately 50% of cases received some form of treatment 9. For symptomatic patients, multiple treatment modalities have been explored including surgery and medical therapy with steroids, immune modulators, anti-inflammatories, hormonal and antifibrotic agents 8 9 21. Our patient received therapy targeted at her DM with both steroids and mycophenolate mofetil with improvement in her symptoms of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is recommendation for non-resolving cases and complicated by bowel obstruction. 1,25 Sharma et al reported that out of 192 cases, 41.7% of cases received surgical resection, 34.9% underwent medical treatment and 17.2% cases were conservatively managed. Of those who received medical 83.5% got steroids and 11.9% received colchicine, tamoxifen and 6-mercaptopurine each.…”
Section: Discussionmentioning
confidence: 99%